(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Mergers and Acquisitions (M&AS) continue to be a significant force in the restructuring of the financial services industry. The Indian Commercial Banking Sector, which has played a pivotal role in the country’s economic development, is currently passing through an exciting and challenging phase. With the onset of economic reforms, the banking sector in India has embarked upon mergers and acquisitions to capture the synergistic benefits like economies of scale and scope, in the face of increasing competition from domestic as well as foreign players and rapid technological developments. Several research studies examine merger related gains in banking and these studies have adopted one of the two approaches, based on either accounting information or market prices.The Indian economic environment provides an advantage to banks and also uniquely accretes value to M&A based transactions proving benefits to bidders unlike in other Bank M&A regimes in the USA. This work provides deeper insight into the linkages between Bank M&A and M&A literature with Indian Banking M&A and reviews the evidence.Mergers and Acquisitions encourage banks to gain global reach and better synergy and allow banks to acquire the stressed assets of weaker banks. A complete combination of two separate corporations involving in a business is referred as business merger. Acquisitions on the other hand are take-over. In this case one company actually buys another company. Through Mergers and Acquisitions banks not only get established brand names, new geographies, complementary product offerings but also opportunities to cross sell to new accounts acquired.The process of Mergers and Acquisitions is not a new to the Indian Banking. The main objective of this paper is to assess the impact of Mergers and Acquisitions in Indian Banking Industry, their position before and after Mergers & Acquisitions and finding out the reasons behind these Mergers & Acquisitions. For the study secondary data is used which has been taken from articles from magazines, newspapers, books and Websites.